ANALISIS EFEKTIVITAS KINERJA KEUANGAN PADA PT. BANK RAKYAT INDONESIA Tbk DAN PT. BANK NEGARA INDONESIA Tbk PERIODE 2016-2020 - Mauk, Sarlince Sandy (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2022)
Abstract The banking sector as part of the financial system plays an important role as an intermediary institution for sectors involved in the economy, therefore the soundness of banks needs serious attention because it involves the interests of many related parties, both owners, government, and society. banking service users. This study discusses the assessment of the effectiveness of the financial performance of Bank Rakyat Indonesia and Bank Negara Indonesia using financial ratios for the 2016-2020 period. The results showed that in terms of the ratio of CAR, Gross NPL, and LDR, BRI and BNI banks met the financial performance effectiveness standards according to Bank Indonesia. BRI's ROA and ROE ratios meet the financial performance effectiveness standards according to the OJK, while BNI's bank for 2020 has not been effective. BRI's NIM ratio is said to be effective while BNI's bank is not effective in 2017-2020. Likewise for the BOPO ratio, the BRI banking BOPO ratio is not effective in 2019-2020. BNI's BOPO ratio for the last five years has not met the financial effectiveness standards according to the OJK. In general, there is no significant difference between the level of effectiveness of the financial performance of BRI and BNI banks.